2011
DOI: 10.1002/jcp.22606
|View full text |Cite
|
Sign up to set email alerts
|

Group X secreted phospholipase A2 specifically decreases sperm motility in mice

Abstract: Different mammalian secreted phospholipases A(2) (sPLA(2) s) are expressed in male reproductive organs and/or in sperm cells but their cellular functions are still not fully characterized. Because several reports indicate a link between cellular lipids and sperm motility, we have investigated the effect of mouse group IIA, IID, IIE, V, and X sPLA(2) s on sperm motility. Among these enzymes, only mouse group X sPLA(2) (mGX sPLA(2) ) acts as a potent inhibitor of sperm motility that decreases track speed (VCL) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 53 publications
0
10
0
2
Order By: Relevance
“…In mature mouse sperm, the group X sPLA 2 (mGX) is located in the acrosome and is released during the AR (24). It specifically improves fertilization and early embryo development (24,27,28).…”
mentioning
confidence: 99%
“…In mature mouse sperm, the group X sPLA 2 (mGX) is located in the acrosome and is released during the AR (24). It specifically improves fertilization and early embryo development (24,27,28).…”
mentioning
confidence: 99%
“…Further they reported that spermatozoa from GX KO mice exhibited lower rates of spontaneous AR and that this was associated with decreased in vitro fertilization (IVF) efficiency due to a drop in the fertilization potential of the sperm and an increased rate of aborted embryos. Mouse GX sPLA 2 acts as a potent inhibitor of sperm motility of both capacitated and noncapacitated sperms [82]. Though the mechanism for this regulation is unclear, this effect of GX sPLA 2 is dependent on its catalytic function and hence might involve changes in phospholipid metabolism.…”
Section: Effect Of Spla 2 S On Male Reproductive Systemmentioning
confidence: 99%
“…Though the mechanism for this regulation is unclear, this effect of GX sPLA 2 is dependent on its catalytic function and hence might involve changes in phospholipid metabolism. It is also found that endogenous GX sPLA 2 is spontaneously released during acrosome reaction and modulates motility of capacitated sperms [82]. Mouse GX sPLA 2 has a unique property of improving fertilization outcome during capacitation [83] and hence has a unique usefulness in improving outcomes in in vitro fertilization.…”
Section: Effect Of Spla 2 S On Male Reproductive Systemmentioning
confidence: 99%
“…La sPLA 2 -GX sécrétée au cours de la capacitation inhibe quant à elle la mobilité flagellaire. Cependant, l'enzyme semble cibler plus particulièrement les spermatozoïdes dont la mobilité est déficiente, en rapport avec une composition lipidique membranaire particulière [25].…”
Section: Rôles Des Phospholipases Dans La Mobilité Spermatiqueunclassified
“…Ces résultats suggèrent que les modifications lipidiques induites par la sPLA 2 -GX au cours de la capacitation sont importantes pour insérer dans le spermatozoïde des messagers lipidiques secondaires favorisant le déve-loppement embryonnaire précoce. La sélection des spermatozoïdes reposerait donc, dans un premier temps, sur la traversée du mucus cervical, puis sur les interactions entre les spermatozoïdes et les cellules épithéliales utérotubaires [28] et, finalement, sur le contrôle de la réaction acrosomique précoce par la sPLA 2 -GX [25].…”
Section: Plcz Une Phospholipase Spermatique Pour L'embryonunclassified